A review of sources, environmental occurrences and human exposure risks of hexachlorobutadiene and its association with some other chlorinated organics. (October 2019) - Zhang, Haiyan; Shen, Yanting; Liu, Wencong; He, Zhiqiao; Fu, Jianjie; Cai, Zongwei; Jiang, Guibin
Abstract: Research on hexachlorobutadiene (HCBD) has increased since its listing in the Stockholm Convention on Persistent Organic Pollutants in 2011. However, thorough reports on recent data regarding this topic are lacking. Moreover, potential associations between HCBD and some chlorinated organics have usually been ignored in previous research. In this review, possible formation pathways and sources, current environmental occurrences and human exposure risks of HCBD are discussed, as well as the association with several organochlorine compounds. The results reveal that unintentional production and emission from industrial activities and waste treatments are the main sources of HCBD. Similar precursors are found for HCBD and chlorobenzenes, indicating the presence of common sources. Although recent data indicates that levels of HCBD in the environment are generally low, risks from human exposure to HCBD, together with other pollutants, may be high. More attention in the future needs to be paid to the mixed contamination of HCBD and other pollutants from common sources. Graphical abstract: Image 1 Highlights: Sources, environmental occurrences and human exposure risks of HCBD are reviewed. Similar formation pathways for HCBD and several organochlorines are summarized. Common sources of HCBD and other pollutants need high attention. Current levels of HCBD contamination in the environment are generally low. Comprehensive risk assessments of HCBD along with coexisting pollutants are proposed. Abstract : This review summarizes current situation of the new POPs HCBD and its association with other pollutants, providing guidance on future research direction in this field.